Temporomandibular Joint Disorders and its Relationship with Parafunctional Habits among Undergraduate Medical and Dental Students - Acharya, Sudeep; Pradhan, Amita; Chaulagain, Rajib; Shah, Ankur (Journal of College of Medical Sciences-Nepal, 2018)
Background: Temporomandibular disorder is a term used to describe problems involving temporomandibular joint, muscles of mastication, occlusion characterized by symptoms such as pain, restricted movements and intermittent joint sound. The present study was conducted to determine prevalence of TMD and to describe its association with parafunctional habits. Materials and Methods: A cross-sectional study was carried out among 345 undergraduate students of KIST Medical College and Hospital. Study population was selected by simple random sampling and the Fonseca Anamnestic Questionnaires were distributed. Data analysis was done in SPSS version 16 . Results: The prevalence of TMD was 47.4% with mild and moderate type of TMD present. The most common habit was chewing gums followed by biting of lips and biting of objects. Statistically significant difference in TMD groups was observed in clenching and grinding of teeth, biting of lips and biting of objects (p<0.001). There was statistically significant association between TMD and the signs and symptoms such as headaches, difficult to open mouth, muscular pain while chewing (p<0.001). Conclusions: A statistically significant association was found between biting of lips, grinding of teeth and mouth breathing with TMD. Keywords: parafunctional habits; prevalence; TMD .